Syncope in Children: Is Rhythm Holter Monitoring Necessary? - Fahrettin Uysal; Özlem Mehtap Bostan; Fatma Çetinkaya; Tuba Deniz; Ergün Çil (Güncel Pediatri)
Introduction: Holter monitoring (HM) is usually used in patients with syncope when etiology cannot be explained with history, physical examination and electrocardiography (ECG). In this study the objective was to evaluate the diagnostic value of HM in children with syncope. Materials and Methods: Databases were collected retrospectively by analyzing the HM results of 3.122 pediatric patients between 2010-2014. Gender, age at diagnosis, detailed clinical history, physical examination, 12-lead electrocardiographic and echocardiographic results were noted using standardized form. Results: The study included 323 patients with syncope with a mean age of 13.21±3.67. There were 199 female and 124 male patients in this study. Among all patients 284 (87.9%) had normal HM results, while 11 (3.4%) patients had abnormal Holter studies that consider to explain as syncope. Three of 11 patients with abnormal Holter results diagnosed through ECG before HM, hence, the diagnostic value of HM was calculated as 2.4%. In contrast, diagnostic value of HM in patients with positive family history was found to be 16.6%. In this study, 7 patients were considered to have long QT syndrome according to their HM findings. Conclusions: Detailed clinical history has a great value in children with syncope. As a result, HM has low diagnostic value if the patients are not in high risk group. However, HM was considered to be important because of concealed long QT syndrome especially if the patient had positive family history and exercise related syncope.